THE ROLE OF ISLAMIC EDUCATION IN DEVELOPING MULTICULTURAL ATTITUDE - Sri Andri Astuti (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Islamic education has a major contribution in developing a mulitcultural attitude in Indonesia which has a diversity of ethnicities, nationalities, races, cultures, gender, and religion. Islamic teachings carried by Islamic education are loaded with multicultural values. Islam highly respects and values ​​differences by instilling an attitude of sympathy, appreciation, respect and empathy. The difference is sunnatullah which must be addressed wisely and gracefully. Through understanding the differences and respecting differences can minimize the occurrence of conflicts such as disputes, divisions, and wars between tribes, nations, races, cultures, genders, and religions.